NFLUENCE OF INTER-FUNCTIONAL COORDINATION ON PERFORMANCE OF INSURANCE ORGANIZATIONS IN KENYA - Waruiru, Esther; Wanjira, Dr. Jane; Namusonge, Dr. Mary Namusonge (European Journal of Business and Strategic Management, 2018)
Purpose: Inter-functional coordination is one aspect that most of the modern day organizations are focusing on as a way of promoting their competitiveness through internal consistency. This involves the harmonization of the firm's operations to create a one uni-operative system. Through the inter-functional coordination, organizations are able to unify their operations and thus enhance better problem solving. The main purpose of the study was to establish the influence of inter-functional coordination on performance of insurance organizations in Kenya Methodology: The philosophical foundation of the study was positivism, and descriptive cross-sectional survey research design was adopted. The target population for the study comprised all the 50 insurance firms while a sample of 384 employees was selected using stratified random sampling. Primary data was collected using questionnaires which were pretested for reliability and validity to determine it suitability for use in the study. Quantitative data was analysed using descriptive and inferential statistics and results presented using charts and tables while content analysis was used for qualitative data. Inferential statistics, corelation, multiple regression analysis were used establish the nature and magnitude of the relationships between the variables and to test the hypothesized relationships. Results: The study findings indicated that inter-functional coordination was statistically significant in explaining organization performance of insurance firms. The study concluded that insurance firms were market oriented through inter-functional coordination and are adopting all measures of marketing orientation to enhance performance. Unique Contribution to Theory, Practice and Policy: The study, therefore, recommends that the insurance firms should ensure that there is a clear and effective organizational structure to enhance smooth flow of operations, ease of communication and sharing of information.